Abstracts (2002)
New approaches towards Efficiency, Productivity and Quality in Management Theory / New approaches towards Efficiency, Productivity and Quality in Management Theory / The new paradigm regarding Science and Management Theory / Game Theory as applied to Administration / A Systemic approach to Territorial Diagnosis /  A prolile 0f Technological Capacity in the Graphical Art, Printing and Publishing Industry / Colombian Industrialisation: a Heterodox Vision /Determinant factors in environmental pollution and the use of natural resources/ Towards Environmental Management of Solid Residues in large Latin-american Cities / A study of the sisal (Fique) chain of production / Organisational culture's importance in implementing and maintaining quality management systems hased on the ISO 9000 standard.